Consumption behaviors of unhealthy food in university students and associated factors - เปียซื่อ, นฤมล (Journal of Nutrition Association of Thailand (Online), 2016)
This study aimed to describe consumption behaviors of unhealthy food and associated factors among university students in Bangkok. Through stratified random sampling, sample included 400 undergraduate students. Data were collected by self-reported questionnaire. Data were then analyzed using frequency, percentage, means, standard deviation, independent t-test, and ANOVA. Results revealed that 67% of the sample were women; 74% enrolled in social related programs while 45.5% stayed in dormitory. The average monthly income was 5,164 Baht and daily food expenditure was 114.55 Baht. Majority of them (83%) had ready-to-eat food. A main reason for their food selection was food that looks good (70.75%). Approximately 43.5% had knowledge of unhealthy food at a fair level, while 39.25% had consumption behavior of unhealthy food. A major factor influencing their food selection was their parents (61%). Factors influencing consumption behaviors of unhealthy food were years in the program (F = 3.168, p = .024), daily food expenditure (F = 8.950, p < .001), and knowledge on unhealthy food (F = 37.856, p < .001). Results indicate the importance of providing knowledge on unhealthy food for students in order to promote appropriate food consumption behavior among them.